Manipulation in Culture Conditions of Nanofrustulum shiloi for Enhanced Fucoxanthin Production and Isolation by Preparative Chromatography - Ayşegül Erdoğan; Ayça Büşra Karataş; Dilan Demir; Zeliha Demirel; Merve Aktürk; Öykü Çopur; Meltem Conk-Dalay (Molecules, 2023)
Microalgae produce a variety of high-value chemicals including carotenoids. Fucoxanthin is also a carotenoid that has many physiological functions and biological properties. For this reason, the cost-effective production of fucoxanthin at an industrial scale has gained significant attention. In the proposed study, fucoxanthin production was aimed to be increased by altering the culture conditions of N. shiloi. The effect of light intensity aeration rate, different nitrogen sources, and oxidative stress on the biomass and fucoxanthin productivity have been discussed. Based on these results, the fucoxanthin increased to 97.45 ± 2.64 mg/g by adjusting the light intensity to 50 µmol/m2s, and aeration rate at 5 L/min using oxidative stress through the addition of 0.1 mM H2O2 and 0.1 mM NaOCl to the culture medium. Fucoxanthin was then purified with preparative HPLC using C30 carotenoid column (10 mm × 250 mm, 5 μm). After the purification procedure, Liquid chromatography tandem mass spectrometry (LC–MS/MS) and UV-vis spectroscopy were employed for the confirmation of fucoxanthin. This study presented a protocol for obtaining and purifying considerable amounts of biomass and fucoxanthin from diatom by manipulating culture conditions. With the developed methodology, N. shiloi could be evaluated as a promising source of fucoxanthin at the industrial scale for food, feed, cosmetic, and pharmaceutical industries.